Understanding Barriers and Facilitators to Compliance with UK Social Distancing Guidelines During the COVID-19 Pandemic: A Qualitative Interview Study. Issue 1 (25th April 2023) - Burton, Alexandra; McKinlay, Alison; Dawes, Jo; Roberts, Anna; Fynn, Wendy; May, Tom; Fancourt, Daisy
Abstract: When followed, there is evidence that social distancing measures play a major role in reducing the transmission of viruses such as COVID-19. However, not all individuals follow the guidance. We explored barriers and facilitators to compliance with UK social distancing guidelines during the COVID-19 pandemic through semi-structured interviews with 116 adults. Data were analysed using reflexive thematic analysis and themes mapped to the Capability, Opportunity and Motivation Model of Behaviour (COM-B). Barriers to compliance included inconsistent rules, caring responsibilities, fatigue, unintended consequences of control measures, and the need for emotional support. Facilitators were informational support and social responsibility. Six themes were both a barrier and a facilitator: lived environment, beliefs about consequences of non-compliance, influence of others, practical support, and trust in government. Reflective motivation, psychological capability, and social opportunity were important drivers for compliance. Measures that enable social support alongside strategies to maintain motivation to comply, provide clear guidance and optimise social cohesion should be promoted.